Large-Eddy Simulation of turbulent heat transfer in a multiple-started helically rib-roughened pipe. (June 2020) - Akermann, Kevin; Renze, Peter; Dietl, Jochen; Schröder, Wolfgang
Highlights: Validation of the numerical approach is achieved by simulations of smooth pipe turbulent flow. Comparison of the ribbed pipe simulation results to measurement and literature data of pressure loss and Nusselt number. The simulations show a good agreement to the measurement data for several Reynolds and Prandl numbers. Numerical approach can be used in the development process of new micro-structured pipes which further enhance heat transfer. Abstract: Large-Eddy Simulations (LES) of single-phase turbulent heat transfer in an internal helically ribbed pipe were performed for R e = 8000 and 16000 and Pr = 5, 7, 9 . The multiple-started rib-roughened pipe has been designed for heat transfer enhancement with low fouling characteristics. Investigations of the domain size were carried out using two-point correlation functions to ensure the usage of an appropriate large domain. Furthermore, the used numerical approach was validated and verified by turbulent heat transfer simulations in a smooth pipe. Detailed information about the flow characteristics and heat transfer in a pipe with a helically ribbed surface are given in this work. The impact of the rip on the turbulent heat transfer is studied in detail. The results of the Nusselt number and pressure loss are compared to results, analytically determined by correlations found in literature, and to measurement data measured by Wieland-Werke AG. A deviation of 0.8 % − 4.8 % between the present Large-Eddy Simulations and measurements of the same pipe geometry has been observed in heat transfer and of 1 % − 7 % in pressure loss. The comparison to literature data has shown that the interpolated results of the correlations differ from the simulations up to 40% in heat transfer and up to 30% in pressure loss. It has shown, that the development of novel structured pipes cannot be covered easily by using results determined by correlations. An enhancement of the heat transfer by a factor 1.7 − 1.9 and a doubled pressure loss compared to turbulent flow in a smooth pipe were determined by the simulations.